Pengembangan Bahan Ajar Pembelajaran Berbasis Storyboard untuk Menulis Cerpen pada Mata Pelajaran Bahasa Indonesia - Nafasya, Riska Resky; Jamilah, Fitri; Wahyuni, Primasari (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
This study aims to: 1) develop teaching materials for learning to write short stories based on storyboards for grade IX junior high school students and 2) explain the feasibility of teaching materials for learning to write short stories based on storyboards. The type of research is research and development (R&D) which refers to the 10 stages of Borg and Gall which is limited to only 7 stages, namely research and information gathering, product development, validation testing, product revision, product testing, product revision, and field testing. The data were obtained from the study of Indonesian language textbooks, interviews, distributing questionnaires or questionnaires, product validation, student limited tests and field tests. The results of this study indicate that: 1) the interest of students in learning to write short stories is still quite low; 2) the product developed is a learning module entitled Writing Short Stories Using Storyboards; and 3) the results of media expert validation on the short story writing learning module using storyboards obtained an average score of 4.70 with a very good category, Indonesian language teacher validation obtained an average score of 4.73 and was categorized as very good, limited trial was obtained the average score is 3.81 and is in the good category, and the field test obtained an average score of 4.25 and is in the very good category. These scores were accumulated and resulted in an average score of 4.37 with a very good category and an eligibility percentage of 87.45%. So, the Write a Short Story Using Storyboard module can be used very reasonably.